Strengthening the Role of Islamic Philanthropy in Promoting Humanitarian Sustainability: A Study in Indonesia and Denmark - Runtiningsih, Sri; Jayanto, Prabowo Yudo; Asrori; Putra, Maulana Kurnia; Asif, Rukhsar (Indonesian Journal of Devotion and Empowerment, 2025)
This community service initiative was implemented through the International Community Service (ICS) 2025 under the theme "Empowering Humanity Sustainability Through Islamic Philanthropy." The primary objective was to enhance awareness and strengthen the global discourse on the role of Islamic philanthropy in fostering economic development, reducing poverty, and promoting social justice. The activity was conducted through an online seminar involving speakers from Indonesia and Denmark, utilizing a participatory approach consisting of presentations, discussions, and participant interaction. The program presented diverse perspectives on zakat’s role in economic growth, poverty alleviation, identity strengthening among Muslim minorities, and the evolution of philanthropic collaboration across sectors. The outcomes demonstrated an increased understanding among participants regarding the adaptive and transformative potential of Islamic philanthropy in various socio-economic settings. This community service program has enhanced participants understanding of Islamic philanthropy and encouraged its application in economic development and community empowerment. The follow-up plan includes continuous mentoring and the strengthening of international collaboration to support the sustainable implementation of Islamic philanthropy.